Interfacial charge transfer on hierarchical synergistic shell wall of MXene/MoS2 on CdS nanospheres: heterostructure integrity for visible light responsive photocatalytic H2 evolution - Kugalur Shanmugam Ranjith; Ali Mohammadi; Ganji Seeta Rama Raju; Yun Suk Huh; Young-Kyu Han (Nano Convergence)
Abstract Energy scarcity and environmental pollution have prompted research in hydrogen generation from solar to develop clean energy through highly efficient, effective, and long-lasting photocatalytic systems. Designing a catalyst with robust stability and an effective carrier separation rate was achieved through heterostructure assembly, but certain functionalities must be explored. In this paper we designed a ternary heterostructure assembly of CdS nanospheres wrapped with hierarchical shell walls of layered MXene-tagged MoS2 nanoflakes, forming intimate interfaces through an in-situ growth process. An in-layered shell wall of MXene with surface-wrapped MoS2 nanoflakes as a core–shell assembly improved the photo-corrosion resistance and accelerated the production of photocatalytic H2 (38.5 mmol g−1 h−1), which is 10.7, 3.1, and 1.9 times faster than that of CdS, CdS–MXe, and CdS–MoS2 nanostructures, respectively. The apparent quantum efficiency of the CdS–MXe2.4/MoS2 heterostructure was calculated to be 34.6% at λ = 420 nm. X-ray and ultraviolet photoelectron spectroscopies validated the electronic states, energy band alignment, and work function of the heterostructures, whilst time-resolved photoluminescence measured the carrier lifespan to evaluate the effective charge migration in the CdS-MXe/MoS2 heterostructure. The dual surface wrapping of MXe/MoS2 over CdS nanospheres confirmed the structural durability that remained intact throughout the photocatalytic reaction, promoting approximately 93.1% of its catalytic property even after five repeatable cycles. This study examined how the MXene heterostructure template improves the catalytic efficiency and opens a new way to design MXene-based durable heterostructure catalysts for solar-energy conversion. Graphical Abstract